Value-for-Money Analysis of Financial Performance at The Faculty of Dentistry, Universitas Padjadjaran - Setiawan, Andi; Fitriani , Laksmi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
This study aims to evaluate the financial performance of the Faculty of Dentistry at Universitas Padjadjaran using the principles of economy, efficiency, and effectiveness, while also identifying key obstacles and proposing potential solutions. A descriptive qualitative method was employed, incorporating value-for-money analysis through the calculation of economic, efficiency, and effectiveness ratios, complemented by interview data. The analysis utilized financial data from 2020 to 2023, including revenue targets and realizations, as well as expenditure targets and realizations. The results show that the average economic ratio reached 99.04%, indicating high economic efficiency. The average efficiency ratio was 54.91%, categorized as very efficient, while the effectiveness ratio averaged 88.03%, falling within the moderately effective category. Interviews revealed challenges in applying these principles, primarily due to the lack of an integrated information system and limited human resources. Nonetheless, these issues could be addressed by recruiting additional personnel. Overall, the findings suggest that the Faculty of Dentistry at Universitas Padjadjaran has generally succeeded in applying the principles of economy, efficiency, and effectiveness in its financial management